في بعض مشتقات االامبيسيلين الدوائية C-O دراسة نظرية لطيف االشعة تحت الحمراء مع حساب طاقات التكسير الحراري لآلصرة - كبة, رحاب ماجد (Al-Nahrain Journal of Science, 2012)
PM3 calculations were carried out for the estimation of vibration frequencies, IR absorption intensities and normal coordinates of some prodrugs (R-ampicilinate, where R is Methyl, Ethyl, Benzyl, 1-Frectosyl, 3-Glycosyl, 3-1,2,5-Trihydroxy Pyran and -CH(CH3)COCH2CH3), all at their calculated equilibrium geometries. Assignment of the vibrations was done depending on the picture of their modes obtained from Gaussian-3 program. Also reaction path for the breakage of the C-O bond (which it connects the drug with its pro), for all the derivatives which were drawn. Comparisons were done among the total energies of the reactants, products, activation energies and transition states. The results show impossible use for ampicilinate prodrugs with (Methyl, Ethyl, Propyl, Benzyl, 1-Fructosyl) groups, to give ampiciline drug on breakage of C-O bond, whereas ampicilinate prodrugs with (3-Glycosyl, 3-1,2,5- Trihydroxy Pyran and 2-Ethyl Carbonate) groups could give an ampiciline drug on breakage of C-O bond.